Indecent assault under the criminal justice system - Mohamad Yunus, Mohamad Ismail (IIUM PRESS, 2017)
The concept of crime has led penologists to believe that the struggle against crimes was above all a struggle against poverty, sickness etc. In other words, it means that if these social evils could be eliminated, the problem of crime prevention would be easy to solve. However, there are certain peculiar categories of crime, which do not respond this hypothesis due to the pervasive tendency of human nature. Sex crime is obviously one among such crimes, which prevails in almost every society. The incidence of sex crimes in the form of indecent assault, rape, sodomy, bestiality adultery, fornication and incest has become too common nowadays. The complexities have enormously increased with the advance of science, civilisation and culture. Modern urbanisation has brought total disintegration of the society, which has led to these serious problems in human life.